The Fifth Generation (5G) of Wireless Communication - Kishk, Ahmed (IntechOpen, 2019)
The Fifth Generation (5G) of Wireless Communication is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of Electrical and Electronic Engineering. The book comprises single chapters authored by various researchers and edited by an expert active in the Electrical and Electronic Engineering research area. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on the fifth generation (5G) of wireless communication, and open new possible research paths for further novel developments.